Revealing the power practices and ideology of pedophiles in pedophile community through transitivity choices - Risaldi, Antok; Santoso, Anang; Syahri, Moch.; Pratiwi, Yuni (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
Among the choices of grammatical forms, the transitive system stands out in the pedophile community. The purpose of this study is to reveal the exercise of power and ideology of pedophiles through their transitive choices. In systemic functional linguistics (SFL), the transitivity system is widely used to analyze isolated clauses and contextual clauses. The data for this research was taken from conversational texts by pedophiles at WordPress Jakongsu from December 2021 to February 2022. Data were collected through netnography approach (Kozinets, 2010), which applies ethnography collection technique in the virtual world. The existed data were compiled in a digital archive. To analyze the data, Fairclough's critical discourse analysis (CDA) model was used (i.e., description, interpretation, and explanation). The findings of the study indicate that pedophiles tend to use clauses of the material process than those of mental and relational processes.